Sistem Jaminan Mutu dan Prediksi pada Rantai Pasok Ikan dari Perikanan Sungai - Ibrahim, Muhammad Rivani; Mustafid, Mustafid (Universitas Diponegoro, 2021)
The supply chain system with quality assurance and fish prediction has important role for producers and consumers regarding the need for fresh fish to be consumed in certain size. Â The research aims to design quality assurance and predictive model for the fish supply chain system so that it is always available to consumers. The Fuzzy Tsukamoto method approach is used to design prediction model for required fish based on the fish provided by fishermen, and Fuzzy Mamdani approach is used to design model for quality assurance of fish needs that consumers need every week and month. This supply chain system is designed with upstream fishermen and fish sellers and as downstream fish retailers and fish consumers, while data analysis uses quantitative data sourced from fishermen and fish sellers and fish consumers. The prediction system and fish quality assurance provide output as a material for decision making in order to obtain information for agents and consumers that they can provide and supply fish as needed. A case study was conducted on the river fishery sector in Kota Bangun District.Â Â